Characteristics of Problem Solving Ability of Students in Integer Operation Material - Runinda Silviana; Dwi Rahmawati; Rina Agustina (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Problem-solving skills have a close relationship with real life and can be used to deal with everyday life. The problems faced by students in one of the Private Junior High Schools in Metro City, specifically grade VII, have diverse problem-solving skills. This study aims to analyze students' problem-solving abilities in analyzing problems using the polya stage with NCTM indicators, namely understanding problems, designing strategies, solving problems, and reviewing solutions. This study uses a descriptive qualitative approach through purposive sampling techniques. A total of 17 students, 7 students were selected as research subjects based on the criteria of the results of the test description of problem-solving abilities in integer operation material. The category of students' abilities is determined based on the number of polya problem-solving stages that are met. The research instrument was in the form of a test of problem-solving ability on integer operation materials and semi-structured interviews. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results of this study show a difference, namely students with high abilities are able to meet all three stages of problem-solving ability, although they have not been completely completed in all aspects, especially in re-examination. Subjects with moderate ability are able to understand the problem and formulate strategies even though the strategies used are not clear, complete the plan and do not write conclusions in the final stage as a re-examination of the solution, while the low category has difficulties from the stage of understanding the problem to the final stage. These findings imply the need for learning that is tailored to the category of students, starting from strengthening the stages of re-examination in high students, consistency in the implementation of plans in medium students to understanding problems in low students.